Trust, Sociability, and Quality of Life of Sub-Saharan African Migrants in Germany - Adedeji, Adekunle; Akintunde, Tosin Yinka; Idemudia, Erhabor S.; Ibrahim, Elhakim; Metzner, Franka (Frontiers in Sociology, 2021)
Poor social integration is associated with poor quality of life among minority groups. The current study hypothesized that trust and sociability may significantly explain the quality of life performance among Sub-Saharan African migrants in Germany. Data from 518 migrants were analyzed. Hierarchical multiple linear regression models were calculated to assess the predictive effect of trust and sociability on aggregate quality of life. Results show that general trust and sociability explained about 21% of the variance in quality of life score (adjusted R2 = .206; p < .001) for the total sample. Socioeconomic and demographic features suggested an added predictive effect of about 8% for total sample (adjusted R2 = .279; p < .001), 10% for male (adjusted R2 = .322; p < .001) and 4% for female (adjusted R2 = .211; p < .001). The results support trust and sociability as essential in connecting to a new environment and enhancing the quality of life.